2009
DOI: 10.1093/eurpub/ckp141
|View full text |Cite
|
Sign up to set email alerts
|

A cost–utility analysis of adding a bivalent or quadrivalent HPV vaccine to the Irish cervical screening programme

Abstract: HPV vaccination has the potential to be very cost effective in Ireland. The quadrivalent vaccine is more cost effective than the bivalent vaccine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 30 publications
3
27
0
Order By: Relevance
“…On the other hand, in developed countries that have been able to control CC incidence and mortality with solid preventive programs, the HPV vaccine is not as favorable from a cost-effectiveness point of view. Ireland, 20 Switzerland, 21 the United Kingdom, 22 and Finland 23 have gross CC incidence rates of less than 10 cases per 100,000 women/year. In these countries, costeffectiveness studies demonstrated an additional cost of more than US$20,000/QALY.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, in developed countries that have been able to control CC incidence and mortality with solid preventive programs, the HPV vaccine is not as favorable from a cost-effectiveness point of view. Ireland, 20 Switzerland, 21 the United Kingdom, 22 and Finland 23 have gross CC incidence rates of less than 10 cases per 100,000 women/year. In these countries, costeffectiveness studies demonstrated an additional cost of more than US$20,000/QALY.…”
Section: Discussionmentioning
confidence: 99%
“…Ireland, Switzerland, the United Kingdom and Finland have gross CC incidence rates of less than 10 cases per 100,000 women per year [23][24][25][26]. In these countries, costeffectiveness studies demonstrated an additional cost of more than US$20 thousand to save one QALY.…”
Section: Strategiesmentioning
confidence: 99%
“…Vaccination of early adolescent girls (aged 11 [19] or 12 years [20][21][22][23] ) with the AS04-adjuvanted HPV 16/18 vaccine was estimated to be cost effective relative to screening alone from a healthcare payer perspective in a number of countries. All analyses used lifetime cohort Markov models with a 1-year cycle length, evaluated direct costs from a healthcare provider perspective, assumed a protective efficacy of »95-98% against HPV types 16 and 18 with a lifetime duration of efficacy, and discounted both costs and benefits.…”
Section: Other Commentsmentioning
confidence: 99%
“…Most analyses also considered the effect of cross protection against other HPV genotypes. [19,20,22,23] The incremental costs per quality-adjusted life-year (QALY) were h17 294 in Finland (year of costing 2006), [19] h9706 in France (2007), [20] h30 460 in Ireland (not reported), [21] h22 055 in Italy (2007), [22] and $US7339 in Singapore (2008). [23] All incremental costs per QALY gained are lower than commonly accepted willingness-topay thresholds of »h30 000-50 000.…”
Section: Other Commentsmentioning
confidence: 99%